Clinical Course of Methylmalonic Aciduria in Siblings: Two Clinical Cases - Olga V. Bugun; Galina P. Bogonosova; Tatyana A. Astakhova; Tatyana A. Bairova; Natalya N. Martynovich; Darya M. Barycova; Tatyana Y. Belkova; Yuliya S. Livadarova; Nanalya I. Sysoeva ("Paediatrician" Publishers LLC, 2024)
Background. Methylmalonic aciduria (MMA) is a rare disease from the group of hereditary metabolic diseases. The MMA clinical picture is polymorphic and meanwhile similar to other metabolic disorders. Determination of specific metabolites in biological fluids and molecular genetic testing are crucial to diagnose this disease. Timely diagnosis mainly determines the treatment efficacy and, therefore, the prognosis of MMA development. Clinical case description. Two siblings with MMA caused by methylmalonyl-CoA mutase deficiency (OMIM #251000) have shown duplication chr6-49459106-T-TA: NM_000255.4c.360dupT (p.Lys121fs) in homozygous state in exon 2 of the MMUT gene. The disease was diagnosed in the first child with underlying metabolic crisis that finally led to irreversible changes in organs and systems and lethal outcome. The diagnosis in the second child was established antenatally, thus, therapy was initiated from the first day of life. Favorable clinical course of the disease was observed during 5 months of follow-up. Conclusion. Timely MMA diagnosis (antenatal or during neonatal screening) is crucial for effective management and relatively favorable life prognosis for infants.